Production and evaluation of the quality of meat and milk in the Republic of Croatia - Kralik, Gordana; Havranek-Lukač, Jasmina; Petričević, Antun (Acta Agraria Kaposváriensis, 1999)
The Republic of Croatia has favourable conditions for the development of animal production. The analysis of the current position takes into account the period from 1990 to 1998, especially from the aspect of meat and milk production. The data show that because of the war in 1991/1992 the number of cattle declined by 46.6%, that of pigs by 25.9% and that of poultry by 41.8% in the period analysed. In the process of the restoration of animal production not only should the number of animals should be increased, but production technology and the choice of appropriate genotypes of animals and the efficiency of production systems should also be improved. In this review activities which influence the enhancement and more rapid development of animal production, such as orientation towards family farming, breeding techniques and government support for the production programmes, are emphasised. With the transition to a market economy the grading of animal products has become a very important task. The Croatian government is drafting new legislation which includes indicators of quality in the payment system. This should influence more rapid progress in the production of some kinds of meat and milk as well as in achieving an increase in product quality.
Keywords: production; evaluation; meat; milk; quality